McDuff and the baby - Wells, Rosemary; Jeffers, Susan (1997)
McDuff enjoys reading the paper with Fred and taking walks in the woods with Lucy, but all that changes when they bring a new baby home.
Keywords: Dogs -- Juvenile fiction; Infants -- Juvenile fiction; Fiction